2018
DOI: 10.1186/s12894-018-0391-y
|View full text |Cite
|
Sign up to set email alerts
|

Expression, localisation and potential significance of aquaporins in benign and malignant human prostate tissue

Abstract: BackgroundTo study the expression pattern, localisation and potential clinical significance of aquaporin water channels (AQP) both in prostate cancer (PC) cell lines and in benign and malignant human prostate tissue.MethodsThe AQP transcript and protein expression of HPrEC, LNCaP, DU-145 and PC3 cell lines was investigated using reverse transcriptase polymerase chain reaction (RT-PCR) and immunofluorescence (IF) microscopy labelling. Immunohistochemistry (IHC) was performed to assess AQP protein expression in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 28 publications
0
21
0
Order By: Relevance
“…It demonstrated that the AQP5 transcripts were not limited to the site of implantation. In previous studies, we suggested the possibility of luminal cells transdifferentiation into cells of mesenchymal characteristics, which could explain the presence of AQP5 on the first day of culture [30,31].…”
Section: Discussionmentioning
confidence: 88%
“…It demonstrated that the AQP5 transcripts were not limited to the site of implantation. In previous studies, we suggested the possibility of luminal cells transdifferentiation into cells of mesenchymal characteristics, which could explain the presence of AQP5 on the first day of culture [30,31].…”
Section: Discussionmentioning
confidence: 88%
“…Development of gastric adenocarcinomas is a stepwise progression of histologic lesions, starting with gastritis, followed by intestinal metaplasia, dysplasia, and eventually invasive adenocarcinoma. AQP3 has been reported to associate with human cancer progression and metastasis, such as pancreatic ductal adenocarcinoma, prostate cancer, cervical intraepithelial neoplasia, and triple-negative breast cancer [22][23][24][25][26]. However, the role of AQP3 and its expression pattern in gastric carcinogenesis remain unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Our results were similar to the studies using anti-AQP3 antibodies prepared from AA180-228 and C terminus peptide of AQP3 in the SCCs of the lung, skin, and oral cavity, UC, prostate adenocarcinoma, and bronchioloalveolar carcinoma (Table 5 ). 17 , 18 , 20 , 29 32 , 34 , 35 , 38 , 39 Degradation of AQP3 protein located near the C terminus part in UC and AA180-228 part of AQP3 in OSCC is associated with a higher grade of the tumors and tumor cell invasion (muscle-invasive UC and OSCC with lymphatic metastasis cases), the underlying molecular mechanism of which remains unclear. 17 , 20 , 34 However, our results were contradictory to those of studies on medullary thyroid carcinoma, hepatocellular carcinoma, pancreatic ductal adenocarcinoma, and triple-negative breast cancer, which suggested increased expression of AQP3 in these carcinomas (Table 5 ).…”
Section: Discussionmentioning
confidence: 99%